The Effectiveness of Schema Therapy on Marital Bond and Hostile Attribution in Women Experiencing Infidelity and Marital Betrayal - Mohammadrahimi Esfarjani, Zahra; Amiri, Majid (Psychology of Woman Journal, 2025)
The purpose of this study was to investigate the effectiveness of schema therapy on marital bond and hostile attribution in women experiencing infidelity and marital betrayal. This study was a quasi-experimental research with a pre-test-post-test design and a control group, followed by a follow-up. The statistical population consisted of all married women who referred to counseling and psychological services centers in Shahreza in 2024 and had experienced infidelity by their husbands. A sample of 30 women was selected using convenience sampling method. Then, 15 women were randomly assigned to the control group and 15 women to the experimental group. Data collection tools included the "We-ness in Romantic Relationships" questionnaire by Cruz et al. (2023) and the "Hostile Attribution Questionnaire" by Arntz et al. (2003). Schema therapy was implemented based on the protocol by Farrell et al. (2018) in 10 sessions, and data were analyzed using SPSS software. The results of the Bonferroni post-hoc test showed that the mean scores of marital bond and hostile attribution differed significantly between pre-test and post-test, and pre-test and follow-up (p<0.05), but not between post-test and follow-up. Therefore, schema therapy was effective in improving marital bond and reducing hostile attribution in women experiencing infidelity and marital betrayal, and this effectiveness was maintained during the follow-up period. It can be concluded that schema therapy can be used to improve marital bond and reduce hostile attribution in women experiencing infidelity and marital betrayal.